Os impactos nos controles internos e nas práticas de governança corporativa de uma empresa concessionária de energia elétrica com a implantação da Lei Sarbanes-Oxley - Carioca, Karla Jeanny Falcão (2008)
Corporate Governance practices have nowadays a fundamental importance in business and can be understood as a set of practices and controls, internal and external, with the aim of improving business management. Because of the scandals in the American market occurred as a consequence of the bad administration and use of irregular account practices, was created the Sarbanes-Oxley act that, among all objectives, try to minimize the risks of internal controls associates with financial reports. This law affected not only American companies but all companies that have stocks negotiated at the New York Stock Exchange. More over, due to the increasing necessity of transparent information, a search was intensified for better improvement in the aspects of Internal Control and Corporate Governance of the companies. The aim of this study is to analyze the impacts of implementation of Sarbanes-Oxley Act in the Internal Controls and Corporate Governance practices in Companhia Energética do Ceará - Coelce, company controlled by a spanish group, which possess trading shares over the New York Stock Exchange and need to be adjusted to the Corporate Governance and Internal Controls practices required for the attendance of the Sarbanes-Oxley Act .This research was made through a study case, with the application of questionnaires and interviews in a group of Coelce´s employees, composed by managers, directors and participants of the management of Internal Control of the company. It was used bibliographical research as theoretic support about Corporate Governance, Internal Controls and Sarbanes-Oxley Act, that fundament the study case done in this study. The conclusion was that the company searched suffered relevant impacts in the Internal Control because them were not adequate to the Act before there was the obligation to attendant it and that the most important impacts in the Corporate Governance practices were not with the implantation of the necessary requisites for the attendant of the Act but with the privatization process that the company passed.